2019
DOI: 10.2174/1573401313666171003150503
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Health Benefits of Catechin from Green Tea (Camellia sinensis)

Abstract: Background: Tea (Camellia sinensis, Theaceae) is the second most consumed beverage in the world. Green tea is the least processed and thus contain rich antioxidant level, and believed to have most of the health benefits. </p><p> Methods: We commenced to search bibliographic collection of peer reviewed research articles and review articles to meet the objective of this study. </p><p> Results: From this study, we found that the tea beverage contains catechins are believed to have a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Syringic acid and catechin, which are related to methyl syringate and epicatechin, respectively, followed in abundance. Health promoting properties such as antioxidant and antiproliferative activities have been found in all these polyphenols (Gheena & Ezhilarasan, 2019;Natarajan et al, 2019;Qu et al, 2020).…”
Section: Mellissopalynology and Physicochemical Characterization Of Zmentioning
confidence: 99%
“…Syringic acid and catechin, which are related to methyl syringate and epicatechin, respectively, followed in abundance. Health promoting properties such as antioxidant and antiproliferative activities have been found in all these polyphenols (Gheena & Ezhilarasan, 2019;Natarajan et al, 2019;Qu et al, 2020).…”
Section: Mellissopalynology and Physicochemical Characterization Of Zmentioning
confidence: 99%
“…These substances can also reduce the formation of free radicals in the body which have an important role in aging and precursing many forms of diseases. Tea also contains many dietary components, including vitamin E, C, fluoride, and potassium [ 4 , 5 ]. Mycotoxins are secondary fungal metabolites that produced by specific strains of mold (fungi) which are famous as potential top priority human's health hazard.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have reported that RA is the predominant phenolic compound found in P. frutescens , and it possesses antioxidant, anti‐allergic, antidiabetic, anticancer, antimicrobial, and anti‐inflammatory properties (Swamy et al., 2018; Zhu et al., 2014). SA, CA, and (+)‐catechin are the phenolic and flavonoid compounds often found in tea, coffee, fruits, vegetables, and plants, which exhibit functional properties such as antioxidant, anticancer, antimicrobial, antidiabetic, and anti‐inflammation (Bagdas et al., 2019; Natarajan et al., 2017; Srinivasulu et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Three phenolic acids and one flavonoid in PFLE were identified and quantified by HPLC-DAD and the results are summarized in Table 1. antidiabetic, and anti-inflammation (Bagdas et al, 2019;Natarajan et al, 2017;Srinivasulu et al, 2018).…”
Section: Hplc-dad Analysesmentioning
confidence: 99%